1988
DOI: 10.1002/bin.2360030104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of structured ward activities on appropriate and psychotic behaviof of chronic psychiatric patients

Abstract: A group of 10 male chronic patients were observed on a psychiatric ward while participating in structured activities (team sports, art projects, and housework) and during comparison time periods in which no activities were present. Broad spectrum behavioral measures obtained with the Time-Sample Behavior Checklist (TSBC) showed that activities produced a 70% reduction in bizarre and inappropriate behavior, as well as a 400-500% increase in productive and appropriate behavior. Performance in activity sessions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…As seen in Table 1, the first publications that included the ATD in group work appeared in the 1980s ( k = 2), with only two more over the next two decades. Wong and colleagues (1988) used an ATD to assess the effects of two types of structured group activities (e.g., team sports, art projects) on bizarre psychotic and appropriate behaviors in 10 male chronic psychiatric patients on a hospital ward. On a random schedule, the group of patients participated in one of three different types of sessions: (a) structured group activities with positive reinforcement (tokens earned through active participation), (b) structured group activities with noncontingent reinforcement (tokens given regardless of the level of participation), or (c) baseline sessions (control sessions in which no structured activity was offered).…”
Section: Review Of Single-case Designs In Group Work Studiesmentioning
confidence: 99%
“…As seen in Table 1, the first publications that included the ATD in group work appeared in the 1980s ( k = 2), with only two more over the next two decades. Wong and colleagues (1988) used an ATD to assess the effects of two types of structured group activities (e.g., team sports, art projects) on bizarre psychotic and appropriate behaviors in 10 male chronic psychiatric patients on a hospital ward. On a random schedule, the group of patients participated in one of three different types of sessions: (a) structured group activities with positive reinforcement (tokens earned through active participation), (b) structured group activities with noncontingent reinforcement (tokens given regardless of the level of participation), or (c) baseline sessions (control sessions in which no structured activity was offered).…”
Section: Review Of Single-case Designs In Group Work Studiesmentioning
confidence: 99%
“…A similar set of educative procedures combined with tangible reinforcement has been used to raise self-care and grooming skills from a near zero level to a daily performance or more frequent basis (Nelson & Cone, 1979; Wong et al, 1988). Recreational activities have been introduced to reduce bizarre vocal and motor behavior (Corrigan, Liberman, & Wong, 1993; Wong et al, 1987; Wong, Wright, Terranova, Bowen, & Zarate, 1988) and increase appropriate leisure behavior (Wong et al, 1988) in psychiatric patients of varied diagnoses including schizophrenia. In an analogous fashion, Bradshaw (2000) and Bradshaw and Roseborough (2004) employed cognitive–behavioral procedures of progressive relaxation and exercise, thought-stopping and self-distraction, cognitive restructuring, and positive self-appraisal to progressively lower ratings of global pathology and to raise ratings of adaptive role functioning.…”
Section: Logical Contradictions and Imprecisionmentioning
confidence: 99%
“…Patients' demeanor changed dramatically during recreational activities, and in these sessions they were indistinguishable from nonpatients. In another study, my colleagues and I (Wong, Wright, et al, 1988) quantified the effect of structured activities on positive behavior and showed that group activities increased socially appropriate and productive behavior 400% to 500% over that recorded during unstructured free time.…”
Section: Recreational Behaviormentioning
confidence: 99%